A study of hotel lobby physical servicescape and guest impression towards hotel / Sabrina Tarmudi and Nor Siah Jaharuddin - Tarmudi, Sabrina; Jaharuddin, Nor Siah (Universiti Teknologi MARA, Perak, 2022)
This paper aims to understand the physical servicescape elements of the hotel lobby and guest impression of hotels. Servicescape's role in the service industry is increasingly important and getting attention in hospitality research. A hotel lobby is the place or meeting point between guests and employees upon arrival. However, less attention has been given to the hotel lobby operationally. The physical environment and ambience of the hotel lobby are critical to impress guests and convey the hotel image. Accordingly, the purpose of this research is to operationalize the construct of the servicescape for the hotel lobby. This study aims to examine the relationship between hotel lobby servicescape towards guest impression. A quantitative study by distributing questionnaires to hotel guests who experienced the hotel lobby servicescape at the hotel will be employed. Analysis of the data collected by using Structural Equation Modeling (SEM) will be used to test the relationships among variables. In addition, it is hoped that this study will shed new light on the relationship between hotel lobby servicescape and guest impression specifically in the hotel industry.